Peralihan Harta Waris oleh Seorang Ahli Waris tanpa Persetujuan Ahli Waris Lainnya (Studi Putusan Mahkamah Agung Nomor 218 K/Pdt/2020) - Fauzan, Ade Ahmad; Guntara, Deny; Abas, Muhamad (Universitas Ekasakti, 2023)
The transfer of rights to an object can be carried out in a real way, meaning that the object obtained can be directly seen and is in the hands of the person concerned, but there is also a transfer of rights that is carried out symbolically or indirectly, only in the form of a letter or certificate, this occurs in immovable objects. The transfer of rights occurs due to the transfer of one person's property rights to another person, for example buying and selling or exchanging or in other ways that are justified by law. The purpose of this study is first to find out the transfer of inheritance according to civil inheritance law in Indonesia and secondly to find out the judge's considerations in the Supreme Court decision number 218 K/Pdt/2020. This study uses a normative juridical approach. The results of research regarding the transfer of inheritance according to civil inheritance law in Indonesia there are two forms, namely the transfer due to the Act and the transition due to a will or testament, then in the Supreme Court Decision Number 218 K / Pdt / 2020 MA stated judex facti, namely the Balige District Court was wrong apply the law so that the Supreme Court cancels and judges itself with a ruling rejecting the Plaintiff's lawsuit (Respondent's cassation).